PENGARUH PROMOSI ONLINE AKUN MEDIA SOSIAL INSTAGRAM @bogardeliveryservice TERHADAP KEPUTUSAN PEMBELIAN JASA BOGAR DELIVERY SERVICE - Crisjuliana Silaban; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The development of technology and information in modern times makes people not free to use technology in their lives, one of them is for trading business. The use of technologies such as the internet can make it easier to introduce the products or services of target audiences. In conducting online promotions through the internet, social media is the most widely used media to promote products or services because it is easy, fast, and efficient. One of the most widely used social media is Instagram. Bogas Delivery Service is one of Pekanbaru's local online motorcycle taxi services that uses online promotions on Instagram. The purpose of this research is to find out how much influence online promotion on Instagram @bogardeliveryservice social media accounts for purchasing decisions on the use of the online motorcycle taxi service Bogar Delivery Service.This research is a quantitative research using regression analysis. The independent variable in this study is online promotion while for the dependent variable is the purchase decision. The population in the study are all followers of @bogardeliveryservice accounts totaling 7,195. According to the Isaac and Michael sample tables with an error rate of 10%, the number of samples is 261 people. The sampling technique in this study used a random sampling technique. The technique of collecting data using questionnaires and documentation. Feasibility test of each instrument using validity and reliability test. Meanwhile, for processing data using the SPSS Windows version 23 program.Based on the results of research on the effect of online promotion on purchasing decisions in the use of the Bogar Delivery Service motorcycle taxi service, the regression coefficient value is Y = 2.619 + 0.607X, with a significance level of 0.000 which is less than 0.05, meaning online promotion through media @bogardeliveryservice Instagram social has a big influence on the Bogar Delivery Service's online motorcycle taxi service purchase decision variables. The magnitude of the effect that occurs is equal to 53.8% and the remaining 46.2% is influenced by other variables not included in the study. With these results, in this study it was found that Ha was accepted and Ho was rejected.Keyword: Online Promotion, Social Media Instagram, Purchase Decisions